Cultivation viability of Allium tuberosum L. in the Western Ghats: insights into crop dynamics, yield and quality - Gavhane, Abhishek D.; Kale, Rajiv B.; Khade, Yogesh; Bhandari, Hem Raj; Gaikwad, Shivam Y.; Singh, Sharadveer; Shabeer T. P., Ahammed; Garde, Yogesh A.; Khandagale, Kiran; Mahajan, Vijay (Frontiers in Plant Science, 2024)
Allium tuberosum, commonly known as garlic chives, is an underutilized Allium species despite its significant culinary value for its mild garlic flavour and therapeutic potential due to the presence of sulphur-containing compounds with antimicrobial, anti-inflammatory, and antioxidant properties. This study assessed the cultivation potential of A. tuberosum in the non-traditional agro-climatic region of the Western Ghats, focusing on the effects of cultivars and seasonal variations on growth, yield, and quality in two-year field trials. Among the accessions tested, A. tuberosum Kazakhstan CGN-1587 demonstrated the highest yield, producing 157.01 tons of green foliage per hectare. Bright sunshine seasons positively influenced both yield and quality, while the monsoon season induced morphological changes such as increased stem length, reduced leaf width, and decreased stem girth, traits generally considered inferior for market quality. The monsoon also led to increased waste generation, highlighting the need for careful management during this period. Nutritional analysis revealed high concentrations of potassium (5355 mg/kg), phosphorus (691 mg/kg), and sulphur (2484 mg/kg), while biochemical profiling identified bioactive compounds such as flavonoids (3.19 mg/g) and organosulfur compounds, including Allyl Methyl Thiosulfinate (269.00 mg/kg), which contribute to the plant's notable health benefits. These findings support the suitability of A. tuberosum for year-round cultivation in the Western Ghats and its potential for commercialization, especially in regions with similar climatic conditions.